Implementation of case-based reasoning in help desk system - Tee, Shih Min (2019)
With evolving of the days, help desk service has become important in a company or an organization as it exists to provide customers or end users with information and support regarding to a company’s or organization’s products and service. Generally, customers will contact the help desk of related issues when they require assistance on providing solution or information to their problem. This leads to existing of help desk system in order to help the help desk personnel respond to customers’ issues or questions more efficiently because of the time consuming when solving the customers’ problem using traditional help desk. Besides of time consuming when solving customers’ problem, the personnel also faced inherently knowledge problem during help desk operation and difficulty in assessing abundant case data without a systematic system. The aim of this research is to design and develop a Help Desk System used by tourism sector by applying Case-based Reasoning (CBR) algorithm. To achieve this aim, CBR algorithm will be studied and implemented in the help desk system to assist the travel agent provide recommendation to customers on selecting the hotel to stay based on customers’ requirements. NetBeans and dataset about travelling retrieved from Open Source Development Network is used for designing and developing the model of the Help Desk System. Moreover, the system model will be tested by several experiments to evaluate its performance. Technicians apply CBR technique to solve a given problem by retrieving the precedent similar cases that are stored into the case library. In my system, it consists of the following steps which are case representation and storage, case matching and retrieval. This research will focus on the case matching and retrieval phase of CBR technique. The methodology being used is the similarity measurement. The result of the testing will be case ID, hotel, price and its calculated similarity. In conclusion, Case-based reasoning is an effective approach to problem solving and learning among the various domains. This is because CBR assists in reducing the effort and time required for knowledge acquisition and representation significantly.